Molecular karyotyping using an SNP array for genomewide genotyping. Issue 12 (9th December 2004) - Rauch, A; Rüschendorf, F; Huang, J; Trautmann, U; Becker, C; Thiel, C; Jones, K W; Reis, A; Nürnberg, P
Abstract : Background: Chromosomal imbalances are a major cause of developmental defects as well as cancer and often constitute the key in identification of novel disease related genes. Classical cytogenetic methods are limited in resolution and dependent on highly skilled labour, while methods with higher resolution, based on molecular cytogenetics approaches such as matrix CGH, are not widely available. Methods: We have developed and evaluated a method we term "molecular karyotyping", using readily available and easy to handle oligonucleotide arrays originally designed for parallel genomewide analysis of over 10 000 SNPs. We show that we can easily and reliably detect unbalanced chromosomal aberrations of various sizes from as little as 250 ng of DNA on a single microarray, based on fluorescence intensity information from clusters of SNPs. Results: We determined the resolution of this method through analysis of 20 trios with 21 previously confirmed subtle aberrations sizing between 0.2 and 13 Mb. Duplications and deletions of at least 5 Mb in size were reliably detectable, but detection of smaller aberrations was dependent on the number of SNPs they contained, thus seven of 10 different deletions analysed, with sizes ranging from 0.2 to 3.7 Mb, were not detectable due to insufficient SNP densitiy in the respective region. Conclusions: Deduction of reliable cut off levels for array peaks in our series of well characterised patients allows the use of the GeneChip Mapping 10K SNP array for performing rapid molecular karyotyping from small amounts of DNA for the detection of even subtle deletions and duplications with high sensitivity and specificity.